Performance Analysis of Data Compression using Two-Dimensional Wavelet Tool - Awatif Ali; Wafa Edradi; Tasneem E. Egreara; Hend A. Eissa (African Journal of Advanced Pure and Applied Sciences, 2025)
This study conducts a comparative investigation of several image compression techniques, namely WDR, ASWDR, STW, SPIHT, and EZW, with particular emphasis on the impact of wavelet filter orders, image content, and compression ratios on compression efficiency. The evaluation framework employs objective performance metrics, including Peak Signal-to-Noise Ratio (PSNR), Mean Squared Error (MSE), and Bits Per Pixel (BPP), derived from the reconstructed images. Experimental validation was carried out using four standard benchmark images, thereby providing a rigorous assessment of the effectiveness and relative performance of the examined algorithms.